Pemberdayaan Masyarakat Untuk Pemanfaatan Bambu sebagai Perkuatan Lereng di Desa Guntur Macan Kecamatan Gunung Sari Lombok Barat - Mahmud, Fathmah; Hariyadi, Hariyadi; Merdana, Merdana; Ngudiyono, Ngudiyono; Kencanawati, Ni Nyoman; Ali, Ahmad Muhammad (Jurnal Gema Ngabdi, 2025)
Guntur Macan Village is a hilly area located in the Gunung Sari sub-district, West Lombok Regency. The sandy hill soil, characterized by a significant slope, lacks cohesion, making the area prone to landslides, especially during heavy rainfall, flooding, or tectonic earthquakes. Landslides are further exacerbated by soil cracks filled with water, either from rain or other sources, which reduce the safety factor compared to soil without cracks. The closer the cracks are to the sliding surface, the more the safety factor decreases. In Guntur Macan Village and the surrounding areas of Gunung Sari sub-district, bamboo is widely planted. Bamboo, being cost-effective and environmentally friendly, can be utilized as a retaining structure to mitigate landslides. This Community Empowerment Program (PKM) commenced with a location survey conducted two weeks before implementation, followed by a two-day execution phase. On the first day, educational sessions were provided, covering topics such as bamboo cutting, preservation, and the construction of bamboo retaining walls. On the second day, bamboo retaining walls were built on residential land in Guntur Macan Village. Through this PKM activity, the residents of Guntur Macan are now capable of constructing bamboo retaining walls to prevent landslides.